"É quase um grito de socorro quando um adolescente chega a cometer um crime": adolescentes autores de atos infracionais para jovens de classe popular - Lima, Fernanda Gonçalves de (2017)
This research aims to identify and describe the social representations that young adults from a popular preparatory class have about adolescents who commits an Infraction. Based in the field of social psychology, we used as principal foundation to the development of this research the Social Representation Theory, to help understanding their perceptions about said adolescents. It’s a descriptive and exploratory study using qualitative methods. Were selected 20 young adults with ages between 18 and 24 years enrolled in two popular preparatory class in Grande Vitória, the participant’s selection was by convenience and access. The data was collected using structured interviews with open questions. It was used phenomenological analysis for psychology investigation to analyze the data found. Even though were found a variety of elements about the adolescent who committed an Infraction, all variations were anchored with poverty, all elements were directly or indirectly related with poverty and with it consequences. Based on the definition of representation as a principle generator in positioning and making a parallel with results found in this work, it is possible to assume that the Young adults interviewed are searching through the study overcome the poverty state, aiming the reduction or extinguish the possibilities in being part of the group of adolescent who commit Infraction, promoting a larger category differentiation.